Influência da irrigação do arroz nas vazões naturais na bacia do Rio Vacacaí - Rosa, Ana Lúcia Denardin da (2009)
This study aimed to apply and assess the simplified methodology used by Paiva et al (2006 b) in the basin of Vacacaí River, to obtain information about natural flows. The analyses were carried out based on hydrological information and the use of geoprocessing techniques to determine the water demands of rice farming and to sub-divide the basin. The study of the use and the occupation of the soil showed that the flood plains of the Vacacaí River are covered by rice fields that occupy 8.06% of the basin area. Factors such as scarcity of rainfall data as well as uncertainty in the demand values adversity affected the goodness of model fit, but it was possible to conclude that the methodology was really efficient in determining the natural flow of sub-basins with approximately 3456 km² of area, and that due to factors that were not considered in the model (e.g. spreading into rivers and storage purposes) it was not possible to obtain better results for sub-basins of larger dimensions. Among the ranges of discretized model, the ones which presented the best results were those with monthly generation and propagation of flow as well as the generation of daily flow and propagation of 7 day average flow, highlighting the monthly simulation due to the smoothing of monthly maximum flows which were not well represented. According to the sensitivity analysis of the parameters of the monthly version model, the values of the parameter kkt showed no sensitivity to the functions studied (coefficient of Nash and Sutcliffe, peak discharge and change in the drained volume), differently from the parameters directly related to superficial flow, Sat and Pes, which were the most sensitive when the peak discharge was considered. From this research, it was concluded that in areas where the number of rice fields is higher the flows in the fluviometric stations are underestimated, the knowledge about natural flows by managers then becomes relevant.